THE EFFECT OF PROFITABILITY, LEVERAGE, AND COMPANY SIZE ON COMPANY VALUE IN ENERGY SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Mutia Zahra; Muslimin; Mohammad Nofal; Anisah (RADJA PUBLIKA, 2026)
This study aims to analyze the effect of profitability, leverage, and company size on the value of energy sector companies for the period 2022-2024. This study uses a quantitative method with a causal associative approach. The research sample consisted of 15 companies selected through purposive sampling, resulting in 45 data observations. The profitability variable is proxied by Return on Assets (ROA), leverage is proxied by Debt to Equity Ratio (DER), company size is proxied by Natural Logarithm (Ln Total Assets), and company value is proxied by Tobin's Q. Data analysis was performed using the EViews 12 program. The results show that profitability and leverage have a positive and significant effect on company value, while company size has no effect on company value.